MONOCLONAL ANTIBODIES AGAINST THE BABESIA BOVIS RAP1 ANTIGEN: OBTAINING AND CHARACTERIZATION - Mukantayev , K.; Tursunov, K.; Adish , Zh.; Kanayev, D.; Tokhtarova, L.; Abirbekov , B. (Eurasian Journal of Applied Biotechnology, 2024)
Bovine babesiosis is a disease caused by parasites of the genus Babesia. One of the main Babesia genera causing disease in cattle, according to the International Office of Epizootics (OIE), is Babesia bovis. Recovered cattle become permanent latent carriers and can be a source of tick infestation and spread of infection. Despite susceptibility and specificity, diagnostic methods such as enzyme-linked immunosorbent assays (ELISA) and indirect fluorescent antibody assays (IFA) have some disadvantages. These methods require a long analysis time, the use of specialized equipment and trained specialists. At the same time, immunochromatographic tests (ICA) are widely used in veterinary practice today. ICA is characterized by a short analysis time, ease of performance and interpretation of results. The main components of the ICA test system are monoclonal antibodies. As a result of the studies, three mAbs against the recombinant Rap1 antigen of B. bovis were obtained. The resulting mAbs have high diagnostic characteristics. A conjugate of colloidal gold with mAbs is capable of detecting the Rap1 antigen of the causative agent of babesiosis in cattle.